2014
DOI: 10.1097/mog.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Nonvariceal upper gastrointestinal bleeding

Abstract: Upper gastrointestinal bleeding from peptic ulcer disease is not a new clinical problem. Yet, the approach to management continues to evolve with the accumulation of data and well designed studies on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…H. pylori infection and the use of nonsteroidal anti-inflammatory drugs (NSAIDs) are independent risk factors for PUB ( 13 ). Eradication of H. pylori can significantly reduce the risk of recurrent peptic ulcer and its complications ( 14 ). Further studies are required to determine whether H. pylori infection is one of the pathogenic factors for PUB in extreme climates.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection and the use of nonsteroidal anti-inflammatory drugs (NSAIDs) are independent risk factors for PUB ( 13 ). Eradication of H. pylori can significantly reduce the risk of recurrent peptic ulcer and its complications ( 14 ). Further studies are required to determine whether H. pylori infection is one of the pathogenic factors for PUB in extreme climates.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were treated with comprehensive routine therapy according to the guidelines for diagnosis and treatment of NVUGIB. [ 9 – 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…Nonvarices upper gastrointestinal bleeding (NUGIB) is one of the most common encountered emergency disorders in daily clinical practice worldwide. [1][2][3][4][5] It is reported that its incidence varies between 50 and 150 cases per 100,000 adults annually. [6][7][8][9] Although its therapeutic managements have developed, its morbidity and mortality rate remain substantial.…”
Section: Introductionmentioning
confidence: 99%